Raw milk cheese as a potential infection source of pathogenic and toxigenic food born pathogens - Cardozo, Marita Vedovelli [UNESP]; Nespolo, Natalia; Delfino, Tammy Chioda [UNESP]; de ALMEIDA, Camila Chioda [UNESP]; Pizauro, Lucas José Luduverio [UNESP]; Valmorbida, Mylena Karoline [UNESP]; Pereira, Natália [UNESP]; de ÁVILA, Fernando Antônio [UNESP] (FapUNIFESP (SciELO), 2021)
The consumption of raw milk cheese has been growing worldwide with S. aureus and E. coli been the leading agents in food poisoning. The present work aims to evaluate the microbiological quality of raw milk cheeses commercialized in Brazil, regarding microbiology safety and enterotoxin gene presence. Forty-three raw milk cheeses samples from five different suppliers were analyzed. Counting and identification of S. aureus, E. coli and Salmonella spp were performed according to BAM from the FDA. Further S. aureus identification was performed by the cydB and Salmonella spp by the invA gene. S. aureus toxin genes (sea, seb, sec, see, ses, seh and sei) and E. coli gene LT, STa, Stb, stx1, stx2, eae, rmpA, wabG, mrkD, kfu, mcgA, fimH and uge were analysed. From the 43 samples analyzed, 18 presented S. aureus with two isolates positive for the tst gene, two for the sec gene, two for the seh gene and four for the sei gene. Thirty-five E. coli and seven. Salmonella spp isolates were obtained. E. coli isolates harbored sta and stx2 genes. The results revealed that raw milk cheeses sold can cause harm consumer’s health and highlights the importance of adoption good hygienic-sanitary practices and consumers awareness.
Keywords: Epidemiology; Food safety; Pathogens; Virulence genes